Transfer of the Indian species formerly included in the genus Lutica Marx, 1891 to Tropizodium Jocqué & Churchill, 2005 and Zodarion Walckenaer, 1826 (Araneae, Zodariidae) - Sankaran, Pradeep M.; Caleb, John T.d.; Sebastian, Pothalil A. (Zootaxa, 2019)
The Indian spider species formerly placed in the zodariid genus Lutica Marx, 1891 are revised. The following new combinations are proposed: Tropizodium bengalensis (Tikader & Patel, 1975) comb. nov., Tropizodium kovvurensis (Reddy & Patel, 1993) comb. nov., Tropizodium poonaensis (Tikader, 1981) comb. nov. and Zodarion deccanensis (Tikader & Malhotra, 1976) comb. nov.. T. kovvurensis comb. nov. is redescribed based on freshly collected female specimens. All the examined type specimens are illustrated and the current status of each type is discussed.